2009 42nd Hawaii International Conference on System Sciences 2009
DOI: 10.1109/hicss.2009.74
|View full text |Cite
|
Sign up to set email alerts
|

Application of Protection Motivation Theory to Adoption of Protective Technologies

Abstract: While most technology adoption models have focused on beneficial technologies, Protection Motivation Theory (PMT) is a potentially valuable model for predicting adoption of protective technologies, which help users avoid harm from a growing number of negative technologies, such as malware. We present a PMT-based model of users intentions to adopt anti-spyware software and test the model on undergraduate student computer users. Results show that perceived vulnerability, perceived severity, response efficacy, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
4
16
1
Order By: Relevance
“…influence the users' behavioral intention to adopt various technologies (Woon et al, 2005;Chenoweth et al, 2009;Ab Rahman and Choo, 2015;Gao et al, 2015;Hsieh et al, 2017;Verkijika, 2018). Hence, we hypothesize the following: H3.…”
Section: Self-efficacymentioning
confidence: 94%
See 2 more Smart Citations
“…influence the users' behavioral intention to adopt various technologies (Woon et al, 2005;Chenoweth et al, 2009;Ab Rahman and Choo, 2015;Gao et al, 2015;Hsieh et al, 2017;Verkijika, 2018). Hence, we hypothesize the following: H3.…”
Section: Self-efficacymentioning
confidence: 94%
“…Perceived severity refers to "the degree of physical harm, psychological harm, social threats, economic harm, dangers to others rather than oneself, and even threats to other species" (Rogers and Prentice-Dunn, 1997). Perceived severity was found to positively affect the individuals' behavioral intention to adopt anti-spyware software (Chenoweth et al, 2009), cloud computing services (Ab Rahman and Choo, 2015) and healthcare wearable devices (Gao et al, 2015). In the context of smartwatch, if students have strong perceptions on the severity of a threat, it can motivate them to avoid security incidents.…”
Section: Perceived Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…When faced with a breach, it is common practice for businesses to request users to reset passwords for all the other accounts where that account information is used (UnderArmour, 2018). Previous research on security behaviors has found support for perceived vulnerability and perceived severity (Chenoweth et al, 2009;Crossler & Belanger, 2014;Liang & Xue, 2010;Martens et al, 2019;Thompson et al, 2017). Therefore, we hypothesize H2: Perceived severity of password loss will be positively related to intention to use password managers.…”
Section: Background and Hypothesesmentioning
confidence: 86%
“…In these cases, the use of antivirus reduces the chance that computing resources are compromised. Previous research has used protective motivation theory (PMT) to explain individuals' intention to use such security tools (Chenoweth, Minch, & Gattiker, 2009;Gurung, Luo, & Liao, 2009;Martens, De Wolf, & De Marez, 2019;Thompson, McGill, & Wang, 2017).…”
Section: Background and Hypothesesmentioning
confidence: 99%